Business statistics : a decision-making approach - Groebner, David F.; Shannon, Patrick W. (Columbus, Ohio : C.E. Merrill Pub. Co., 1981)
The book provides a meaningful statistics book for students and professionals who are interested in learning not only how the statistical techniques are used but why decision makers need to use them. in this text many fundamental statistical techniques that have application in the functional areas of business including accounting, finance, marketing, management, real estate and economics have been introduced.
Includes bibliographical references and index.
nmn, 21/07/16
Loans
Keywords: Commercial Statistics; Statistical Decision